Vila Autódromo in dispute: subjects, instruments and strategies to reinvent the space | Vila Autódromo em disputa: sujeitos, instrumentos e estratégias para a reinvenção do espaço - Sánchez, Fernanda; Oliveira, Fabrício Leal de; Monteiro, Poliana Gonçalves (Revista Brasileira de Estudos Urbanos e Regionais, 2016)
The struggle of the residents in Vila Autódromo to reinvent their territory, violently affected by the onslaught of urban restructuring during the times of Olympic urbanism in Rio de Janeiro, is taken as an emblematic case of the production of conflictual space. The present article describes the various instruments and strategies that the residents and their supporters have used in order to resist the current city project. The imaginative capacity of the subjects over recent years has helped to bring the case into the public sphere on several different levels: local, national and international. The present article is made up of the following sections: a brief description of Vila Autódromo as a disputed territory; the media as an active tool in the production of space; institutional violence on the territory; places for communicating the struggle; and insurgent territorial grammars. In the final considerations a number of the key ideas are taken up so as to emphasize the transformative, emancipatory learning possibilities for all those who have participated within the process.